Equestrian sports safety: An update on safety equipment and event medical coverage - Gould, S.; Roy, I. R.; Gabriel, F. D.; Lowe, R.; Lin, C. Y. (Current Sports Medicine Reports, 2025)
Equestrian sports are associated with high rates of major injury compared to collision and powered two-wheel sports. Advancements in rider and horse safety equipment and the implementation of comprehensive emergency action planning standards may help mitigate injuries, particularly in regard to the Olympic disciplines of dressage, show jumping, and three-day eventing covered in this review. Personal safety equipment to consider includes helmets, safety and air vests, and horse tack including safety stirrups, acoustic dampeners, and breakaway reins. Equestrian event medical coverage requires emergency action planning, partnership with local emergency medical services, and cooperation of interprofessional teams. Safety coordinators and medical providers may be tasked with providing first aid to spectators in addition to stabilizing and triaging crush trauma, traumatic brain injuries or spinal injuries, or fractures in competitors. Stationary and mobile medical units, proper medical equipment, acute spine stabilization protocols, and communication systems are critical components of equestrian medical coverage.